6.4. By using Standard formulae , expand the following ii (2x + 3/x-1)^2 ​

Question

6.4.
By using Standard formulae , expand the following

ii (2x + 3/x-1)^2

in progress 0
Evelyn 3 months 2021-10-15T17:49:47+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-10-15T17:51:13+00:00

    Step-by-step explanation:

     =  {(2x +  \frac{3}{x - 1} )}^{2}  \\  =   4 {x}^{2}  +  \frac{9}{ {(x - 1)}^{2} }  +  \frac{12x}{x - 1}  \\  =  \frac{4 {x}^{2}  {(x  -  1)}^{2} + 9 + 12x(x - 1) }{ {(x  -  1)}^{2} }  \\  =  \frac{4x(x - 1)(x(x - 1) + 3) + 9}{ {x}^{2} + 1 + 2x }  \\  = \frac{ (4 {x}^{2}  - 4x)( {x}^{2}  - x) + 12 {x}^{2}  - 12x + 9}{{x}^{2} + 1 + 2x }  \\  =  \frac{4 {x}^{4}  - 4 {x}^{3} - 4 {x}^{3}  + 4 {x}^{2} + 12 {x}^{2} - 12x + 9 }{ {x}^{2} + 2x + 1 }  \\  =  \frac{4 {x}^{4}  - 8 {x}^{3}  + 16 {x}^{2} - 12x + 9 }{ {x}^{2} + 2x + 1 }

Leave an answer

Browse

14:4+1-6*5-7*14:3+5 = ? ( )